Теоретичні та практичні аспекти ведення інформаційної війни у ЗМІ - Кіца, Мар’яна; Свинаренко, Ганна; Kitsa, Mariana; Svynarenko, Hanna (Видавництво Львівської політехніки, 2019)
Досліджено поняття інформаційної війни, здійснено порівняльний аналіз дефініцій інформаційної війни та інформаційного протиборства, визначено особливості та суть цих понять. На основі аналізу 63 публікацій у російських інтернет-ЗМІ різного спрямування зроблено висновок, що характерною для зазначених ЗМІ була негативна позиціящодо подій в Україні, загальна тематика матеріалів і їх ідеологічне спрямування не змінилися і сьогодні. У ході дослідження ми дійшли висновку, що поняття інформаційного протиборства ширше і охоплює поняття інформаційної війни як одного із двох його складників. Дослідники стверджують, що можна виокремити інформаційно-технічний та інформаційно-психологічний складники інформаційного протиборства. У ЗМІ використовується пропаганда та дезінформація, серед них особливо популярним є метод викривленої інтерпретації фактів, подання інформації без джерела, приховування джерела інформації тощо. Інколи канали поширення інформації, які використовує українська сторона в інтернеті, атакують хакери. Це тимчасово призупиняє діяльність ЗМІ, що призводить і до втрати аудиторії та втрачання можливості оперативного подання інформації. Російські ЗМІ змагаються з українськими за більший сегмент аудиторії, щоб здобути панування в інформаційній сфері, адже ширша аудиторія сприяє перемозі в інформаційній війні. Щодо практичної складової, то матеріали російських інтернет-видань найчастіше висвітлювали питання: діяльності ЗСУ, культурно-історичних надбань, сучасного українського політичного режиму, співпраці України з ЄС, США та НАТО, реформи в українському суспільстві, життя на окупованих територіях та в анексованому Криму, ідеологію, притаманну українському суспільству, події в зоні АТО, корупцію в Україні.

In the article the concept of information warfare is analyzed, it is also done comparative analysis of definitions of information warfare and information confrontation, the features and essence of these concepts are determined. Based on the analysis of 63 publications in Russian Internet media of different directions, it was concluded that the media in these media had a negative attitude to the events in Ukraine and the general themes of the materials, and their ideological orientation has not changed for today. During the study, we came to the conclusion that the concept of information confrontation is wider and includes the concept of information warfare as one of its two components. Researchers claim that it is possible to distinguish between information and technical and informational and psychological components of information confrontation. Media uses propaganda and misinformation, among which the method of distorted interpretation of facts, the provision of information without source, the hidden source of information, etc. is especially popular. Sometimes the channels of information dissemination used by the Ukrainian side on the Internet are attacked by hackers. It temporarily suspends the activities of the media, which leads to the loss of the audience and the loss of the ability to submit information operatively. Russian media compete with Ukrainians for a larger segment of the audience to gain dominance in the information sphere. After all, a larger number of audiences contributes to victory in the information warfare. As to the practical component, the materials of Russian Internet publications most often covered the issues: the activities of the Armed Forces, cultural and historical achievements, the current Ukrainian political regime, Ukraine’s cooperation with the EU, the US and NATO, reforms in Ukrainian society, life in the occupied territories and annexed Crimea, an ideology inherent in Ukrainian society, events in the ATO zone, corruption in Ukraine.
Theoretical and practical aspects of providing information warfare in mass media
Keywords: інформаційна війна; новини; АТО; онлайн-ЗМІ; ідеологія; information warfare; news; ATO; online media; ideology; 659.3 (477)